The future of scholarship on race in organizations - King, Eden B.; Roberson, Quinetta M.; Hebl, Michelle R. (Emerald Publishing Limited : Information Age Publishing, Inc., 2022)
"Since the term "workforce diversity" was first coined in the 1990s, the topic has received consistent and increasing attention by researchers. Over the last 30 years, a body of theory and research has amassed which recognizes diversity as an important work unit characteristic and explored its influence on organizational functioning and performance. Despite these advancements, the field is at a critical juncture where new ideas, emphases, theories, predictions and approaches are needed to propel our understanding of the meaning, import and functioning of diversity in organizations. Accordingly, this volume looks to the future of diversity work, both with regard to the content of the chapters and to the contributors. We endeavored to give a voice to emerging scholars who are the future of our field and can help to set a future research agenda to push our understanding of diversity in organizations. The scholars raise new and provocative questions about race in organizations that deliberate on the state of our science, our understanding of complex experiences of race, and a more nuanced view of race in terms of intersectionalities. Overall, each of these chapters provokes the status quo and, in so doing, offers a fresh perspective on the study of diversity in general and race and racism more specifically. We believe the end result is a more comprehensive exploration of the phenomenon and the development of an exciting future research agenda"-- Provided by publisher.
Keywords: Racism in the workplace.; Discrimination in employment.; Management -- Research.; Business & Economics -- Diversity & Inclusion.; Racism and racial discrimination, Anti-racism.; Diversity, equality and inclusion in the workplace.; elektronické knihy; electronic books